Síntese de carvão ativado a partir de resíduos de tecido de algodão - Narita, Carla Kazumi Carrascoza Yoshida (2022)
Cotton fabric waste originating from the clothing industry is recognized, within the branches of Brazilian industrial activities, as one of the biggest environmental pollutants, in view of the high volume of waste generation with few reuse solutions, most of which are destined for legal and even illegal disposal in Brazil. The Apucarana region is considered the largest national producer of caps and currently accounts for 25% of clothing production in Paraná. Among the fabrics used, fabrics with cotton composition stand out. When discarded incorrectly, they can take more than 10 years to decompose. The current disposal of these generated waste must be carried out in an industrial landfill, but often the disposal is carried out incorrectly in parks and/or rural areas of the city. The need to search for alternatives for the reuse of these wastes, through reuse and/or recovery processes, becomes essential in promoting improvements in the management of waste from these industries, benefiting the reduction of environmental impact. Within the recognized environmental technologies, the synthesis of activated carbon from textile industrial waste becomes a promising alternative for the destination of this waste. This project aimed to apply environmental technologies for the transformation of industrial waste from cotton fabric through the synthesis of activated carbon by pyrolysis, diversifying impregnation methodologies and your aplication in the adsorption of industrial dye used in textile industries in the process of processing of cotton fabrics. The carbons were produced with and without chemical activation with phosphoric acid and sodium hydroxide. The charcoal that showed the best result was activated with phosphoric acid, followed by activated charcoal with sodium hydroxide, while charcoal without activation did not show satisfactory results.